CLEANING EFFECTIVITY OF SEVERAL SURFACTANS TO PESTISIDES RESIDUES ON FRESH APEL FRUITS - Endang Lukitaningsih; B.S. Ari Sudarmanto; Sri Noegrohati (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2002)
Intensification efforts in farming to increase productivity must consider the pesticide utilization, especially insecticide and herbicide. Several pestisides which are still used include carbofuran and organochlorine, some of them have lipofilic properties and might harm to human health. Therefore, an effort is required to washing off pesticides from farming products is one of the effort which can be performed. Since pesticides has lipofilic properties, therefore cleaning pesticides with water is not sufficient. Surfactant is required to increase washing off ability of water. Wash off ability of several surfactants circulated on the market i. e. SL, ML and A were investigated. The result showed that the wash off ability values of surfactants to DDT residues on fresh apples were 79.18 %, 75.19 % and 67.49 % for SL, A and ML respectively. The wash off effectiveness of surfactant A, SL and ML to -metrine were 85.29 %, 80.48 % and 64.47 % respectively.Key words: pesticide, cleaning efficiency surfactant, DDT, -metrine.